2017
DOI: 10.1016/j.bpg.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Do smoking and alcohol behaviours influence GI cancer survival?

Abstract: Little is known about the role of alcohol and smoking in GI cancer survival compared to GI cancer development. We systematically reviewed the evidence for a role of smoking and alcohol in prognosis among GI cancer patients and inform whether smoking or alcohol cessation interventions or guidelines for GI cancer patients are likely to improve prognosis. A total of 84 relevant studies were identified. Continued smokers, particularly heavy smokers, had worse prognosis than never smokers in most GI cancers. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…This meta-analysis also investigated the association between these lifestyle factors and survival in other cancers of the digestive tract. Results demonstrated that cigarette smoking was associated with poorer survival in patients with colorectal, gastric, or pancreatic cancer, hepatocellular carcinoma, or esophageal squamous cell carcinoma [14]. Alcohol consumption was associated with a poorer survival in patients with esophageal squamous cell carcinoma or hepatocellular carcinoma [14].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This meta-analysis also investigated the association between these lifestyle factors and survival in other cancers of the digestive tract. Results demonstrated that cigarette smoking was associated with poorer survival in patients with colorectal, gastric, or pancreatic cancer, hepatocellular carcinoma, or esophageal squamous cell carcinoma [14]. Alcohol consumption was associated with a poorer survival in patients with esophageal squamous cell carcinoma or hepatocellular carcinoma [14].…”
Section: Introductionmentioning
confidence: 98%
“…However, only four published studies, including relatively small numbers of patients, have investigated the association between tobacco smoking, alcohol consumption, and esophageal adenocarcinoma survival [10][11][12][13]. Our working group has published a recent meta-analysis combining two of these studies, which demonstrated no significant difference in esophageal adenocarcinoma survival in neveralcohol drinkers compared to moderate alcohol drinkers (HR 1.34 95% CI 0.95-1.89) [14]. Similarly, there were no associations with survival in esophageal adenocarcinoma patients who were current (HR 0.99 95% CI 0.73-1.36) or former (HR 0.88 95% CI 0.68-1.14) smokers, compared to never smokers [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of the VA Surgical Quality Improvement Program database demonstrated, over a 6 year period, that current smokers with GI malignancies were significantly more likely to experience surgical site infections (SSIs), combined pulmonary complications, pneumonia, failure to wean from ventilator, reintubation, and return to the operating room . A separate systematic review of 84 studies has also demonstrated that current smokers, particularly those who smoke heavily, have worse survival outcomes than never smokers in most GI cancers . In addition, continued tobacco use during chemotherapy has been shown to exacerbate drug toxicity/side effects, impair immune function, and increase the incidence of infection .…”
Section: Introductionmentioning
confidence: 99%
“…heavily, have worse survival outcomes than never smokers in most GI cancers. 2 In addition, continued tobacco use during chemotherapy has been shown to exacerbate drug toxicity/side effects, impair immune function, and increase the incidence of infection. [3][4][5][6][7][8] Furthermore, cancer survivors who continue to smoke also demonstrate a higher risk than non-smokers for developing a second cancer.…”
mentioning
confidence: 99%